2021
DOI: 10.1016/j.gete.2019.100147
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of a crack driven by viscous fluid taking into account plastic effects in the process zone

Abstract: In this paper the problem of redirection of a crack driven by viscous fluid under mixed mode loading is considered.The loading includes the classical Modes I -III and the hydraulically induced tangential traction on the fracture walls. The effect of the plastic deformation of the near tip zone is accounted for. Different criteria to determine the fracture deflection angle are examined and compared.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…and the fluid front velocity in the form (30). The four unknowns p(r, t n+1 ), w(r, t n+1 ), a(t n+1 ), and (t n+1 ) of non the linear problem (58) have been determined by means of a staggered approach, as detailed in box 3. Therein, µ and j stand for the counter of the outer loop devoted to compute the crack radius and the counter of the inner loop devoted to compute the fluid front position, respectively.…”
Section: Space and Time Discretization Of Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…and the fluid front velocity in the form (30). The four unknowns p(r, t n+1 ), w(r, t n+1 ), a(t n+1 ), and (t n+1 ) of non the linear problem (58) have been determined by means of a staggered approach, as detailed in box 3. Therein, µ and j stand for the counter of the outer loop devoted to compute the crack radius and the counter of the inner loop devoted to compute the fluid front position, respectively.…”
Section: Space and Time Discretization Of Governing Equationsmentioning
confidence: 99%
“…A hybrid scheme is employed: the elasto-hydrodynamic problem is solved implicitly, while the crack front is explicitly updated with the velocity computed at previous iteration. To escape the limitation of propagation in pure mode I loading conditions, recent investigations on mixed mode hydraulic fracture propagation can be found in [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…If we categorize the plasticity effects into two groups: i) those that affect the rock splitting ahead of the fracture tip and as such contribute to the crack length extension and, ii) the effects of plastic deformation of the bulk of the fractured material, the question arises whether accounting only for the first group can be sufficient for modeling at least in the small yield cases. The question becomes even more vital if we recall that the plastic deformation effects in the near tip zone can substantially affect fracture development, for example the crack redirection (Wrobel et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, it has a significant effect on the evaluation of the fracture Energy Release Rate (ERR). It was demonstrated that the differing tip asymptotics offered an alternative physical explanation for the transition in fracture growth behaviour which occurs over time (between viscosity and toughness dominated regimes), while a follow-up investigation demonstrated a possible impact on fracture redirection [Perkowska et al, 2017, Wrobel et al, 2021b and examined the dependence of these effects on fluid rheology [Wrobel et al, 2021a].…”
Section: Introductionmentioning
confidence: 99%
“…Below we give a short overview of results obtained in the study of hydraulic fracture with shear stress induced upon the crack walls by the fluid, which provides the motivation for this work. In the original paper of , alongside a later extension to the mixed-mode case in [Perkowska et al, 2017, Wrobel et al, 2021b, it was demonstrated that the asymptotics of the displacement and stress fields near the crack-tip (r → 0) are…”
Section: Introductionmentioning
confidence: 99%